The Emperor and the Saint : Frederick II of Hohenstaufen, Francis of Assisi, and Journeys to Medieval Places - Cassady, Richard F., 1919- (Book collections on Project MUSE., 2011)
"The Emperor and the Saint is a vivid place-by-place telling of the life and times of the most enlightened, creative, and dynamic ruler of Medieval Europe, Frederick II of Hohenstaufen. St. Francis, who shared with Frederick a love of the natural world and was baptized in the same cathedral in Assisi, is a parallel and contrasting presence. Cassady enthusiastically guides the reader through the history and legends, pausing to describe the architecture of a cathedral, to marvel at the atmosphere of a town, to recommend the best place for a quiet picnic of local fare. A man of insatiable curiosity, Frederick spent hours developing his knowledge of science and religion, art and philosophy. He traveled the length and breadth of Europe, even going to the Holy Land where, as commander of a Crusade, he negotiated a treaty with Sultan al-Kamil of Egypt, nephew of the great Saladin. Both respected and reviled, Frederick achieved great heights and faced grave disappointments. When Frederick died in December 1250, he was robed in the white habit of a Cistercian monk to demonstrate his connection to personal, political, and religious worlds."--Publisher's website